2017
DOI: 10.4314/sajas.v47i2.12
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of growth, milk and manure production in Norwegian dairy goats in one highland of Tanzania 30 years after introduction

Abstract: Dairy goats have been imported into Tanzania since the 1960s to improve the milk production of Small East African (SEA) goats through crossbreeding. The SEA goats have poor genetic potential for milk. Although crossbreeding programmes started in the early 1980s, most were abandoned or failed for a number of reasons, including lack of performance records, which were important for the design and management of breeding programmes for dairy goats. This study was designed to evaluate growth, lactation, and manure y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…Variation in body weight of kids in different breeds could be attributed to the genetic content of parents due to their affect by the doe breed (20) and sire breed (40). Body weights of kids revealed in this study lay within the range (1.09-4.42 kg) for BWT, (4.8-23.0 kg) for WWT, and (7.35-26.72 kg) for WT6M which found by earlier studies conducted at several countries using different breeds (5,13,21,26,28,29,30,31,33,34,35,38,41,46,55,57). Although there was no significant effect for age of doe on all studied traits (Table 2), however with using Scheffe's test to diagnosing the significant differences between the levels of age of doe, it appears that does aging 3.5 years gives kids having significantly higher BWT, while the differences among the kids born from does with different ages were not significant in their WWT and WT6M (Table 1).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Variation in body weight of kids in different breeds could be attributed to the genetic content of parents due to their affect by the doe breed (20) and sire breed (40). Body weights of kids revealed in this study lay within the range (1.09-4.42 kg) for BWT, (4.8-23.0 kg) for WWT, and (7.35-26.72 kg) for WT6M which found by earlier studies conducted at several countries using different breeds (5,13,21,26,28,29,30,31,33,34,35,38,41,46,55,57). Although there was no significant effect for age of doe on all studied traits (Table 2), however with using Scheffe's test to diagnosing the significant differences between the levels of age of doe, it appears that does aging 3.5 years gives kids having significantly higher BWT, while the differences among the kids born from does with different ages were not significant in their WWT and WT6M (Table 1).…”
Section: Resultssupporting
confidence: 80%
“…Heaviest weights of single births at later weights in comparison with twin and triple births could be related to their weights at birth (48). Earlier studies reported that single born kids are significantly heavier than twin born kids at birth (21,25,26,27,41,46,57). While other studies didn't noticed the significant effect of type of birth on birth weight of kids (13,55).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The results of analysis of variance in Table (2) show that fixed effects on the studied traits were generally significant (P<0.01or P<0.05), except for the effect of parity on WW and ADG of Baladi kids which were not significant. The results found in this study are in agreement with those reported by Alade et al 2008, Boujenane and El Hazzab 2008, Otuma and Osakwe 2008, Rashidi et al 2008, Hermiz et al 2009, Zhang et al 2009, Thiruvenkadan et al 2009, Sodiq et al 2010, Supakorn et al 2011, Mohammadi et al 2012, Andries 2013, Bedhane et al 2013, Deribe and Taye 2013, Kuthu et al 2013, Osman 2013, Bingol et al 2014, Ray et al 2015, Gupta et al 2016, Syahirah et al 2016, Bolacali et al 2017, Msalya et al 2017, and Rout et al 2018.…”
Section: I-fixed Effectssupporting
confidence: 91%
“…Keeping dairy goats has several advantages for the farmers, such as improved income from the sales of live animals and manure. Manure has commercial value, enabling farmers to sell it and earn additional income [16]. Most of the farmer respondents also had crop farming including vegetable farming, therefore they used the manure to increase the plant production.…”
Section: Resultsmentioning
confidence: 99%